ANALISIS PENGENDALIAN KUALITAS PRODUK POLYURETHANE SANDWICH PANEL DENGAN METODE OLD SEVEN TOOLS DI PT. ABC - Suparjo, Suparjo; Febrianti, Ervina (JHP17 (Jurnal Hasil Penelitian), 2019)
PT.ABC is a manufacturing company that manufactures Plyurethane sandwich panels (PSP). PSPis widely used in several manufacturing industries as insulation walls in the refrigeration room. The coolingroom is usually used to store products so they are not easily damaged. In the PSP production process, thereare often defective products. These defects can occur due to operators, methods, machines, and theenvironment. In this study identification of the types of defects that may occur in the production process ofPSP is carried out. In addition, the causes of defects that occur to be given appropriate improvementproposals are also sought. The method used in this study is Seven tools. The results of this study can beused as a direction for companies to improve their production processes.Keywords: Quality Control, Seven Tools, defects Products